Antibiotic Use and Resistance Development: Exploring Livestock Owners' Knowledge, Attitudes and Practices in south-western Nigeria.
Antibiotic injudicious use and resistance development remains a growing public health concern globally putting the livestock industry and human health at stake, given the resulting increasing emergence of resistant strains of pathogenic bacteria. Despite this, the role of livestock owners who manage the majority of the national herds in most developing countries especially Nigeria remains largely un-investigated. We conducted a qualitative study among 216 randomly selected livestock owners in south-western Nigeria to explore their knowledge, attitudes and practices on antibiotic use and resistance development using semistructured questionnaires. Data were analysed using SPSS version 15.0. The results revealed indiscriminate use of antibiotics by the livestock owners on ready-for-sale cattle. Only 49.54% had good knowledge which was significantly associated with tertiary education (p = 0.01) and 81.02% were unaware of antibiotic withdrawal period. Also, approximately two-thirds (63.89%) had poor attitudes with only 11.11% concerned with the need to observe withdrawal periods. In addition, 91.67% claimed that their veterinarians had never advised them to observe withdrawal period and 95.37% had never observed it. Poor professional attitudes of the so-called veterinarians as well as lack o f law enforcement against uncontrolled sales of veterinary drugs were attributed to the livestock owners' poor knowledge, attitudes and practices. The role of livestock owners should be considered when designing programmes towards preventing antibiotic injudicious use and resistance development. Furthermore, efforts geared towards regulating sales of veterinary drugs as well as enforcement of veterinary professional ethics are needed to safeguard antibiotic effectiveness in both animals and humans, now and in the near future.